Імунно-запальні предиктори розвитку діастолічної дисфункції лівого шлуночка у хворих на ревматоїдний артрит в поєднанні з артеріальною гіпертензією - Данюк, Інна Олександрівна; Риндіна, Наталія Григорівна; Данюк, И. А.; Рындина, Н. Г.; Daniuk, I. O.; Ryndina, N. G. (My University, 2021)
Метою роботи стало визначення діагностичної цінності показників перекисного окиснення ліпідів, ендотеліальної функції та системної запальної відповіді щодо виявлення діастолічної дисфункції лівого шлуночка та діагностики випоту в порожнину перикарда у хворих на ревматоїдний артрит в поєднанні з артеріальною гіпертензією. Об’єкт та методи. Досліджено 93 пацієнта з ревматоїдним артритом в поєднанні з артеріальною гіпертензією II стадії. Хворим проводили ультразвукове дослідження серця, в крові оцінювали стан перекисного окиснення ліпідів, концентрацію прозапальних цитокінів, показники ендотеліальної функції. Целью работы стало исследование диагностической значимости показателей перекисного окисления липидов, эндотелиальной функции и системного воспалительного ответа в выявлении диастолической дисфункции левого желудочка, и в диагностике выпота в полость перикарда у больных ревматоидным артритом в сочетании с артериальной гипертензией. Объект и методы. Было проведено обследование 93 пациентов с ревматоидным артритом в сочетании с артериальной гипертензией II стадии. Больным проводили ультразвуковое исследование сердца, в крови оценивали состояние перекисного окисления липидов, концентрацию провоспалительных цитокинов, показателей эндотелиальной функции. Результаты и выводы. После проведения Эхо-КС у 79 больных были установлены признаки нарушения диастолической функции левого желудочка (первая подгруппа), а у 14 пациентов признаков диастолической дисфункции левого желудочка не установлено (вторая подгруппа). Выявлено достоверное увеличение концентрации асимметричного диметиларгинина на 6,3%, интерлейкина-1β (ИЛ-1β) на 35,3%, интерлейкина-10 (ИЛ-10) на 24,3%, соотношение ИЛ-1β / ИЛ-10 на 62,0%, С-реактивного белка (СРБ) на 52,6% и достоверное уменьшение суммарных метаболитов NO на 36,9% в подгруппе больных ревматоидным артритом в сочетании с артериальной гипертензией и признаками диастолической дисфункции левого желудочка по сравнению с больными без таковой. Hypertension is the most common concomitant disease in patients with rheumatoid arthritis. Diastolic dysfunction of left ventricle is an important predictor of chronic heart failure, which can be asymptomatic for a long time. Therefore, it is advisable to detect diastolic dysfunction of left ventricle as early as possible, which can slow the progression of chronic heart failure. The purpose of the study was to determine the value of lipid peroxidation, endothelial function and systemic inflammatory response markers for diagnostic of diastolic dysfunction of left ventricle and for diagnostic of pericardial effusion in patients with rheumatoid arthritis combined with hypertension. Materials and methods. 93 patients with rheumatoid arthritis in combination with stage II hypertension were studied. The ultrasound examination of heart was performed. The serum laboratory markers of lipid peroxidation, concentration of pro-inflammatory cytokines, markers of endothelial function were determined. Results and discussion. Signs of diastolic dysfunction of left ventricle were found in 79 patients and no signs of diastolic dysfunction were found in 14 patients. It was detected that there was a significant increase of concentration of asymmetric dimethylarginine by 16.3%, interleukin-1β by 35.3%, interleukin-10 by 24.3%, the ratio of interleukin-1β / interleukin-10 by 62.0%, C-reactive protein by 52.6% and there was a significant decrease of total nitric oxide metabolites by 36.9%, nitrires by 37.5% and nitrates by 37.0% in patients with signs of diastolic dysfunction of left ventricle compared to the patients without diastolic dysfunction of left ventricle (p <0.01). It was found that the levels of isolated double bonds, diene conjugates, diene ketones, schiff bases and malonic aldehyde in patients with diastolic dysfunction of left ventricle were significantly higher by 24.4%, 25.2%, 20.4%, 17.6% and 21.4% respectively compared to the corresponding markers in patients without signs of diastolic dysfunction of left ventricle (p <0.01). The levels of vitamin A, vitamin E and catalase in patients with diastolic dysfunction of left ventricle were significantly lower by 18.2%, 27.4% and 13.4% compared to the corresponding markers of patients with normal left ventricle diastolic function (p <0.01). The highest predictor value for the diagnostic of diastolic dysfunction of left ventricle was detected in interleukin-1β area under the ROC curve 0.882, sensitivity 72.15% and specificity 100%, 95% CI [0.798-0.939] at the optimal distribution point >9.67 pg/ml and in asymmetric dimethylarginine area under the ROC curve 0.879 sensitivity 75.95% and specificity of 100%, 95% CI [0.795-0.937] at the optimal distribution point >0.715 μmol/l.
Иммунно-воспалительные предикторы развития диастолической дисфункции левого желудочка у больных ревматоидным артритом в сочетании с артериальной гипертензией
Immune-Inflammatory Predictors of Diastolic Dysfunction of Left Ventricle in Patients with Rheumatoid Arthritis Combined with Hypertension
I. O. Daniuk - 0000-0002-4596-5709; N. G. Ryndina - 0000-0002-8060-3789.
Keywords: ревматоїдний артрит; артеріальна гіпертензія; діастолічна дисфункція лівого шлуночка; ревматоидный артрит; артериальная гипертензия; диастолическая дисфункция левого желудочка; rheumatoid arthritis; hypertension; iastolic dysfunction of left ventricle